Factores de riesgo para mal nutrición en niños/as de educación inicial en centros educativos del área de influencia del Centro de Salud Dra. Mabel Estupiñán en el año 2012 - Córdova Villacís, Luisa A. (2013)
The population of this research consisted of 216 children under five school of the area of influence of the Health Center Dr. Mabel Estupiñán 2012-2013 school years, in the city of Machala. The sample was calculated in a number of 138 children which were selected according to the formula sampling interval.